2008
DOI: 10.12930/0271-9517-28.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Advising is Advising: Toward Defining the Practice and Scholarship of Academic Advising

Abstract: Academic advising has emerged as a distinct interdisciplinary field and profession, but the description of its role has recently relied on analogies and metaphors. While helpful in clarifying practice, their continual use obscures the uniqueness of academic advising and masks the importance of the scholarship that underlies its practice. We use the development of archaeology as a distinct profession and scholarly field to highlight critical developments in academic advising and draw examples of key aspects in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 28 publications
0
38
0
1
Order By: Relevance
“…Defining the field. Statements articulating advising as an educative venture helping students to discover their passions, talents, and capabilities abound (Danis & Wall, 1987Huggett, 2000;Schulenberg & Lindhorst, 2008;Trombley & Holmes, 1981), but ultimately, ''the definitions of academic advising equal the numbers of postsecondary institutions'' (Cate & Miller, 2015, p. 41). Articulation of one central and succinct, yet comprehensive, definition has proven a very difficult endeavor for scholars in the field.…”
Section: Characteristics Of Professionalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Defining the field. Statements articulating advising as an educative venture helping students to discover their passions, talents, and capabilities abound (Danis & Wall, 1987Huggett, 2000;Schulenberg & Lindhorst, 2008;Trombley & Holmes, 1981), but ultimately, ''the definitions of academic advising equal the numbers of postsecondary institutions'' (Cate & Miller, 2015, p. 41). Articulation of one central and succinct, yet comprehensive, definition has proven a very difficult endeavor for scholars in the field.…”
Section: Characteristics Of Professionalizationmentioning
confidence: 99%
“…Despite some early concerns regarding the professionalization of advising (Trombley & Holmes, 1981), most discourse about the field transpired after the turn of the 21st century. The perspectives expressed since 2000 have ranged from those based on the potential for academic advising as an academic discipline (Kuhn & Padak, 2008) or a field of inquiry (Habley, 2009) to a consideration of problematic comparisons of academic advising to other professional endeavors (Schulenberg & Lindhorst, 2008). In 2010, Shaffer, Zalewski, and Leveille penned the important article ''The Professionalization of Academic Advising: Where Are We in 2010?''…”
mentioning
confidence: 99%
“…In 2003, Kansas State University developed an online graduate certificate and in 2008 offered a master's degree program. Although many scholars have described academic advising as a professional endeavor (AikenWisniewski et al, 2015;Habley, 2009;Kuhn & Padak, 2008;McGill, 2013;McGill & Nutt, 2016;Schulenberg & Lindhorst, 2008), in the past few years, the authors of two papers have posited that academic advising does not fit all the characteristics of a profession Shaffer et al, 2010). In analyzing academic advising through the lens of four stages of professionalization from Wilensky (1964)-creating occupations, establishing schools, forming associations, and ratifying codes- Shaffer et al (2010) concluded that the chartering of NACADA (Stage 3) predated the establishment of the requisite schools and body of scholarly knowledge (Stage 2).…”
mentioning
confidence: 99%
“…Since the late 1990s, advisors have pushed to engage in scholarship with the purpose of developing a ''professional, academic identity'' (Schulenberg & Lindhorst, 2010, p. 24). As a result, a few dominant paradigms have emerged and shaped current theory and practice; however, these frameworks also contributed to an indistinct identity of advising programs at institutions of higher education (Schulenberg & Lindhorst, 2008). For example, in his landmark study, Crookston (1972Crookston ( /2009) drew a distinction between developmental and prescriptive advising.…”
Section: Sean Bridgen Penn State New Kensingtonmentioning
confidence: 99%
“…Hagen (2005) encouraged practitioners to renew their thinking about advising: ''Once the metaphorical leap is made to view the student before you as a 'text,' then all of the truth claims of hermeneutics become available for your use'' (p. 5). The literature suggested that advisors, who come from a wide range of academic disciplines, tap into the wisdom gained from their own fields and experiences to build theories unique to academic advising (Hagen, 2005;Lowenstein, 1999Lowenstein, , 2005Schulenberg & Lindhorst, 2008). Musser (2006) offered an example of a new approach in her description of the used-systems theory as a construct to extend the understanding of academic advising.…”
Section: Sean Bridgen Penn State New Kensingtonmentioning
confidence: 99%